2016
DOI: 10.1007/s40894-016-0035-y
|View full text |Cite
|
Sign up to set email alerts
|

What Explains Correlates of Peer Victimization? A Systematic Review of Mediating Factors

Abstract: Being accepted by peers is central to health and wellbeing among adolescents whereas being the subject of peer/bullying-victimization can be perceived as significant interpersonal stress, resulting in compromised adjustment concurrently and long-term. Unfortunately, little is known about mechanisms that explain why peer victimization goes ''under the skin''. This systematic review aims to summarize the research on mediating pathways. A total of 65 articles were selected that explicitly examined mediation of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 107 publications
(124 reference statements)
2
6
0
Order By: Relevance
“…As with other reviews (e.g. Kretschmer, 2016), a dependence on cross-sectional methods was a feature of the work identified. This impedes our ability to identify causal relationships between peer-victimization, appraisals, and adjustment.…”
Section: Ecological Frameworksupporting
confidence: 52%
“…As with other reviews (e.g. Kretschmer, 2016), a dependence on cross-sectional methods was a feature of the work identified. This impedes our ability to identify causal relationships between peer-victimization, appraisals, and adjustment.…”
Section: Ecological Frameworksupporting
confidence: 52%
“…This finding supports the rejection sensitivity model [ 16 ], which suggests that adolescents who develop rejection sensitivity based on interpersonal stressors are more likely to develop externalizing or internalizing symptoms. Thus, adolescents who internalize the experience of cybervictimization may particularly experience an increase in rejection sensitivity [ 17 , 53 ]. Consequently, they may use the Internet, an anonymous virtual space, to connect with others without pressure and to avoid or reduce their anxiety about future social interactions [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis of quasi-experimental evidence found that the effect of bullying on achievement was small (Schoeler et al, 2018), suggesting resilience of victimized children in the long-term. A review of the correlates of bullying suggests that emotional factors might have a larger role than social-cognitive processes in explaining the relationship between bullying and achievement and internalizing outcomes (Kretschmer, 2016), and this conclusion might also help us explain the small effect sizes found.…”
Section: Discussionmentioning
confidence: 99%